Upaya Peningkatan Kualitas Putusan Hakim Agung Dalam Mewujudkan Law And Legal Reform - Nunuk Nuswardani (Jurnal Hukum IUS QUIA IUSTUM, 2009)
Law and legal reform is not only about the supreme court (Mahkamah Agung) governance but also the socializing and the restructuring of the implementation of the new decision by judge. It has many problems that really need consideration. Many gaps are found in the implementation of new judges’ decision (vonnis) on the restructuring of the supreme court (Mahkamah Agung) development. It can be the result of the previous judges’ decision (vonnis). This article aims at seeking a good and reasonable solution of applying the act number 3 of 2009 concerning the optimal restructuring of the supreme court (Mahkamah Agung).Key words: supreme-court, judges, decision, law and legal reform